(untitled) (Промышленный Транспорт Казахстан, 2025)
This article proposes policy alternatives to address the ineffectiveness of implementing measures to improve the investment climate in Kazakhstan to attract investors. In order to assess the above alternatives, five criteria selected - efficiency, implementation cost, political acceptability, public support, and time of implementation.